2012
DOI: 10.1242/jeb.066498
|View full text |Cite
|
Sign up to set email alerts
|

The visual control of landing and obstacle avoidance in the fruit flyDrosophila melanogaster

Abstract: SUMMARYLanding behavior is one of the most critical, yet least studied, aspects of insect flight. In order to land safely, an insect must recognize a visual feature, navigate towards it, decelerate, and extend its legs in preparation for touchdown. Although previous studies have focused on the visual stimuli that trigger these different components, the complete sequence has not been systematically studied in a free-flying animal. Using a real-time 3D tracking system in conjunction with high speed digital imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
159
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 45 publications
18
159
0
Order By: Relevance
“…Diverse taxa of flying insects use visual cues to decelerate smoothly (and thus reduce impact forces) when landing (Baird et al, 2013;Srinivasan et al, 2000;van Breugel and Dickinson, 2012), and the relatively simple control strategy of maintaining a constant rate of image expansion has been proposed as potentially universal, allowing smooth landing on a surface of any orientation (Baird et al, 2013). Our results confirm that bumblebees flying in still air follow a pattern of smooth deceleration consistent with that shown for honeybees [ Fig.…”
Section: Effects Of Wind On Landing Speed and Body Orientationsupporting
confidence: 84%
See 1 more Smart Citation
“…Diverse taxa of flying insects use visual cues to decelerate smoothly (and thus reduce impact forces) when landing (Baird et al, 2013;Srinivasan et al, 2000;van Breugel and Dickinson, 2012), and the relatively simple control strategy of maintaining a constant rate of image expansion has been proposed as potentially universal, allowing smooth landing on a surface of any orientation (Baird et al, 2013). Our results confirm that bumblebees flying in still air follow a pattern of smooth deceleration consistent with that shown for honeybees [ Fig.…”
Section: Effects Of Wind On Landing Speed and Body Orientationsupporting
confidence: 84%
“…Previous studies in honey bees (Apis mellifera) and fruit flies (Drosophila melanogaster) have demonstrated that the visual system plays an important role in controlling approach speed to landing surfaces (Evangelista et al, 2010;Srinivasan et al, 2000), as well as triggering key landing behaviors (van Breugel and Dickinson, 2012). In particular, recent work has shown that insects regulate flight speed during landing by the relatively simple strategy of maintaining a constant rate of image expansion (Baird et al, 2013), causing flight speed to decrease smoothly to zero as the landing target draws closer.…”
Section: Introductionmentioning
confidence: 99%
“…Honeybees have no difficulty either in landing on a dancing flower blown by the wind or an artificial moving target [18]. Flies are known to fixate their targets [48] and to land on them using visual cues [49]. Our biomimetic approach to robotic flight guidance in unsteady environments, which differs drastically from those based on more classical solutions, may help future flying robots to acquire some autonomy at a very low cost: the present tethered robot did not need any inputs about the groundspeed, groundheight, platform speed or platform height, for instance, to be able to land safely on a vertically and horizontally oscillating target.…”
Section: Resultsmentioning
confidence: 99%
“…We think a more plausible explanation is that the butterflies are physically robust enough that they simply have no need to land softly, at least over the range of flight velocities observed in this small arena. This may be a rather common feature of insect flight; when fruit flies land on a vertical post, over a third of landings are 'crashes' where the head or wing contacts the surface before the legs (van Breugel and Dickinson, 2012). This question could be clarified by investigating behaviours such as leg and proboscis extension, which are performed in anticipation of imminent contact.…”
Section: Descent Velocity Controlmentioning
confidence: 99%
“…These approaches are generally not suitable for insects because their compound eyes typically exhibit little binocular overlap, poor spatial resolution and fixed-focus optics. Given these constraints, a more viable alternative is to use motion cues (van Breugel et al, 2014): when the animal is performing a translational movement, nearby objects will move more quickly on the retina than distant ones and hence depth can be estimated.…”
Section: Introductionmentioning
confidence: 99%